Realism and the Crisis of Individualism in Jack London’s “Martin Eden” - Kakharova , Mohigul (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article discusses “Martin Eden” (1909) by Jack London as a realistic novel that portrays the tragic fate of an individual who achieves intellectual and spiritual maturity yet becomes disillusioned with society. The novel is considered to be an autobiographical novel exploring how London reflects elements of his own life in the protagonist. The protagoniost Martin Eden tries to educate himself to gain the love of his girlfriend in the novel. The novel traces Martin’s transformation from an uneducated working-class youth into a self-taught intellectual driven by love, ambition, and an intense desire for self-improvement.